2009
DOI: 10.1111/j.1365-2966.2009.14557.x
|View full text |Cite
|
Sign up to set email alerts
|

On the jet contribution to the active galactic nuclei cosmic energy budget

Abstract: Black holes release energy via the production of photons in their accretion discs but also via the acceleration of jets. We investigate the relative importance of these two paths over cosmic time by determining the mechanical luminosity function (LF) of radio sources and by comparing it to a previous determination of the bolometric LF of active galactic nuclei (AGN) from X‐ray, optical and infrared observations. The mechanical LF of radio sources is computed in two steps: the determination of the mechanical lu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 47 publications
4
58
1
Order By: Relevance
“…Less straightforward is to compile a kinetic luminosity function. It has been done however by Merloni & Heinz (2008), Cattaneo & Best (2009) and Mocz et al (2012). The accretion history is inferred from the radiant luminosity functions, and some assumption is made connecting that to the kinetic power history.…”
Section: The Kinetic Luminosity Functionmentioning
confidence: 99%
“…Less straightforward is to compile a kinetic luminosity function. It has been done however by Merloni & Heinz (2008), Cattaneo & Best (2009) and Mocz et al (2012). The accretion history is inferred from the radiant luminosity functions, and some assumption is made connecting that to the kinetic power history.…”
Section: The Kinetic Luminosity Functionmentioning
confidence: 99%
“…Knowledge of the kinetic power of active galactic nucleus (AGN) jets is vital for quantifying the energetics of AGN feedback and its effect on the host galaxy formation and evolution (Croton et al 2006;Cattaneo & Best 2009;Shabala & Alexander 2009). This kinetic jet-mode of feedback is dominant at the present epoch, whilst the radiative quasarmode was prevalent in the early universe (z ∼ 2-3; Fabian 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The number density of AGN cannot exceed that of their potential hosts: this argument has been used by Mauch & Sadler (2007) and Cattaneo & Best (2009) to constrain the low luminosity behavior of their RLF. They found that a break must occur at a radio luminosity log(Pr/ W Hz −1 ) ∼ 19.5 and 19.2, respectively.…”
Section: The Radio Agn Luminosity Functionmentioning
confidence: 99%